Hyperhomocysteinaemia in Behçet's Disease - Amira Hamzaoui; Olfa Harzallah; Rim Klii; Silvia Mahjoub (Biochemistry Research International)
Objectives. The aim of this study was to investigate if hyperhomocysteinaemia is a contributive risk factor for the pathogenesis and the activity of Behçet's disease (BD). Design and Methods. Fifty four patients fullfiling the criteria of the International Study Group for BD were enrolled. Fifty healthy volunteers matched for age and sex with the BD group were included as a negative control group. Patients, with any condition that might affect plasma homocysteine concentration, were excluded. Results. Mean serum homocysteine concentration was significantly higher in patients with BD than in the healthy controls (𝑃<.001), in patients with active disease (𝑃=.04), and in masculine gender (𝑃=.05). There was no significant difference between homocysteine level and clinical involvement. Conclusions. We demonstrated that plasma total homocysteine level (tHcy) is increased in BD and correlated with disease activity. No association was found between homocysteine levels and clinical involvement.